Transforming growth factor beta modulates the expression of collagenase and metalloproteinase inhibitor. - Edwards, D R (1987)
Exposure of quiescent MRC-5 human fibroblasts to growth factors such as epidermal growth factor, basic fibroblast growth factor or embryonal carcinoma-derived growth factor resulted in the induction of mRNA transcripts encoding the metalloproteinases collagenase and stromelysin and the specific metalloproteinase inhibitor TIMP, whilst expression of collagen and fibronectin was relatively unaffected. Exposure of quiescent cells to growth factors in the presence of transforming growth factor beta (TGF-beta) resulted in inhibition of collagenase induction and a synergistic increase in TIMP expression. TGF-beta alone did not significantly induce metalloproteinase or TIMP expression. These effects on mRNA transcripts were reflected in increased secretion of TIMP protein and collagenase activity. Nuclear run-off analysis of growth factor-induced transcription revealed that the TGF-beta modulation of TIMP and collagenase expression was due to transcriptional mechanisms. The observations suggest that TGF-beta exerts a selective effect on extracellular matrix deposition by modulating the action of other growth factors on metalloproteinase and TIMP expression.